Perlindungan Hukum terhadap Kasus Kekerasan Berbasis Gender Online di Era Pandemi Covid-19 - Benedicta Gabriella Aurelie; Eti Mul Erowati; Elly Kristiani Purwendah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
Gender equality in Indonesia is a very serious problem, because of the patriarchal culture that develops in society. With the development of information and communication technology, various forms of crime have also adapted. One example is the emergence of a new form of gender-based violence, namely Online Gender-Based Violence (KBGO). Online gender-based violence has been a global phenomenon since the early days of internet use. It has become a serious problem, and the COVID-19 pandemic has made things worse. During the COVID-19 pandemic, cases of online gender-based violence increased drastically. This is due to situations and conditions where activities that could previously be carried out directly, must be carried out online or online such as work, teaching and learning, and others. In addition, social media platforms are now very insecure because of the large number of users whose accounts are not based on real identities. In handling it, it is also not enough to only use pre-existing regulations, because it will only become a boomerang for the victims. Cases of online gender-based violence should be a serious concern for all parties.